A Model of Potential Encounters in the Workplace: The Relationships of Homophily, Spatial Distance, Organizational Structure, and Perceived Networks. (July 2017) - Kabo, Felichism W.
Potential face-to-face encounters are foundational to most workplace social interactions. There is little resolution on the question of what factors are antecedent to these encounters. This study examines the association of potential encounters with homophily, spatial distance, organizational structure, and perceived networks. Real-time, fine-grained data were collected using ultrawide-band location-tracking technology deployed at a knowledge-intensive subunit of a global manufacturing firm. The organization comprised scientists and engineers responsible for environmental policy, and emissions reporting and trading at the parent company. Potential encounters were constructed from the location data and modeled on the factors above using dyadic network regression models. The results show that spatial distance, organizational structure, and perceived network ties are all significantly related to potential encounters. Surprisingly, the homophily variables were nonsignificant. The contributions of this research regarding the relationship between potential face-to-face encounters and homophily, spatial distance, organizational structure, and perceived networks are discussed.